Legal Culture and its Role in Civil Society Formation - AKHMETOV, Arman Serikovich; ZHAMULDINOV, Victor Nikolaevich; KOMAROV, Oleg Evgenievich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).03, 2018)
The purpose of this article is to present a comprehensive study and analysis of existing scientific approaches to the study of the phenomenon of legal culture in the process of civil society formation, as well as to develop certain recommendations for improving the level of the legal culture of the population. The methodological basis of this work is formed by a set of general scientific and special legal methods of cognition. The presented scientific approaches to the study of legal culture as a social phenomenon made it possible to develop an author’s justified position based on the existing achievements of researchers in the field of the nature and essence of the legal culture of civil society. Based on domestic and foreign sources, the research allowed us to analyze the existing approaches to the study of legal culture, to determine the main factors that can form the basis for the development of the level of the legal culture of the population as well as to develop a number of measures, which will help to form citizens’ legal awareness and increase their legal literacy. The process of forming the legal culture of the population is quite complex and multifaceted, since it affects the relationship between society and the state and has its own characteristics.